Peningkatan Kesadaran Dan Praktik Pengelolaan Sampah Berbasis Rumah Tangga Di RT 30 RW 05 Kelurahan Betungan - Chairunisa, Putri Aulia; Rahmadania, Friska; Gaol, Vandri Salomo Lumban; Dianestari , Gea; Hanila, Siti; Susena, Karona Cahya; Soleh, Ahmad (Universitas Dehasen Bengkulu, 2025)
Sustainable waste management, such as waste sorting and processing, among the community. This condition is exacerbated by the behavior of throwing waste without sorting, piling, and burning which damages the environment. Effective waste management should start from the source by implementing the 3R concept (Reduce, Reuse, Recycle), which relies heavily on active community participation. Objectives and Methods: This community service program aims to increase awareness and facilitate household-based waste management practices in RT 30 RW 05, Betungan Village. This study uses a descriptive qualitative approach supported by simple quantitative data. The subjects of the service are heads of families and housewives. Data were collected through questionnaires (pre-test and post-test), observation sheets, semi-structured interviews, and documentation. The implementation procedure includes preparation, implementation (socialization, education, waste sorting and composting training, mentoring, monitoring), and evaluation and reporting. Data analysis was carried out using simple quantitative methods to compare the pre-test and post-test, as well as thematic qualitative methods for interviews and observations. Results and Conclusions: This PKM activity succeeded in showing a significant increase in knowledge, changes in attitudes, and community awareness regarding waste management. This is evident from the implementation of waste sorting practices in households, the establishment of community waste management initiatives, and the creation of a cleaner and healthier environment in RT 30 RW 05. Various interventions such as comprehensive socialization, practical training (sorting and composting), facility facilitation, and continuous monitoring have proven effective in addressing the problem of low awareness and practices of waste management. The success of this program underscores the importance of education and active community participation as the key to effective waste management at the local level.